Pembentukan Sikap Kewirausahaan Mahasiswa Melalui Program Wirausaha Merdeka di Universitas Muhammadiyah Makassar: Forming Students’ Entrepreneurial Attitudes Through the Independent Entrepreneurial Program at Muhammadiyah University of Makassar - Milda Milda; Mulyadi Mulyadi; Musbaing Musbaing (Al-Musannif, 2023)
The number of unemployed college graduates is increasing because they generally expect to be employees and are not interested in entrepreneurship. The purpose of this study was to analyze (1) the formation of students' entrepreneurial attitudes through the independent entrepreneurial program and (2) the opportunities and challenges faced by students in the program. The research method used is qualitative, with a case study approach. The object of the research is the Muhammadiyah University of Makassar as the only organizer of the independent entrepreneurial program in eastern Indonesia, which was selected and beat the leading universities. The informants in this study were purposively selected committee members and students participating in the independent entrepreneurial program. The results showed the formation of students' entrepreneurial attitudes through workshops, business partner onboarding, entrepreneurial experience, and the expo. This program provides opportunities for students to acquire entrepreneurial knowledge, create their own businesses, and build networks with entrepreneurs. The challenge faced by students is convincing business partners of their product ideas and deadlines for preparing products for the expo.